Penerapan Modul Elektronik Sigil untuk Meningkatkan Kompetensi Pengetahuan dan Kemampuan Representasi Grafik Siswa - Amelia, Fariza; Ekawati, Elvin Yusliana; Fauzi, Ahmad (Jurnal Materi dan Pembelajaran Fisika, 2023)
This study aims to: (1) Describe the improvement of knowledge competence of students in class XI MIPA 2 SMA Negeri 5 Surakarta in the 2021/2022 academic year through the application of the Sigil electronic module, (2) Describe the improvement of the graphic representation ability of students in class XI MIPA 2 SMA Negeri 5 Surakarta in the 2021/2022 academic year through the application of the Sigil electronic module. The research design used is class action research (PTK) using the Kemmis and Mc. Taggart model and organized in two cycles. The data collection technique used interviews, tests, documentation and document review techniques. Data analysis techniques used qualitative and quantitative analysis. Data validity techniques used instrument validity and triangulation techniques. The results showed that the application of the Sigil electronic module based on Saintifik on the material Elasticity and Hooke's Law can improve the knowledge competence and graphic representation skills of students in class XI MIPA 2 SMA Negeri 5 Surakarta in the 2021/2022 academic year. The percentage of knowledge competency completeness increased from 35.29% in the pre-cycle stage, to 61.76% in cycle I, and reached 100% in cycle II. The percentage of achievement on each indicator of students' graphic representation ability also increased from 4 indicators achieved in cycle I, then in cycle II all indicators reached the research target.